Mercury distribution and speciation in two lagoons with different pollution and eutrophication conditions in Taiwan. (July 2020) - Hung, J.-J.; Hung, C.-S.; Wann, C.-K.; Hung, P.-Y.; Kuo, F.
Abstract: This study explored biogeochemical processes controlling the distribution of mercury (Hg) species in two lagoons with different pollution and eutrophication conditions in southwestern Taiwan. The eutrophication and pollution levels were higher in the Dapeng Bay than in the Chiku Lagoon, engendering a higher particulate Hg concentration and enrichment factor in the Dapeng Bay. The concentration range of total dissolved Hg (HgTD ) and reactive Hg (HgR ) was comparable between the lagoons, but the concentration of particulate Hg (HgP ) was higher in the Dapeng Bay. HgR and HgTD abundance was primarily controlled by the availability of dissolved oxygen (DO) and biological absorption. In addition to pollution (which elevated HgP concentration), biological absorption and/or adsorption rather than lithogenic processes more likely regulated the HgP concentration. The effect of Hg pollution may superimpose on that of DO on the distributions of HgR and HgTD and may enhance HgP formation in the Dapeng Bay. Highlights: Dapeng Bay had higher eutrophication and Hg pollution levels than did Chiku Lagoon. DO availability and biological absorption likely regulated HgR and HgTD distributions. Hg pollution elevated and biological (not lithogenic) processes regulated HgP. Hg pollution may superimpose on DO effects on HgR and HgTD distributions in Dapeng Bay.